Nilai-nilai yang Digunakan Siswa dalam Pilihan Karir - Sutoyo Imam Utoyo (Universitas Negeri Malang, 2016)
The main purpose of this study was to explore values applied by students in choosing a career and the ways in which the counselors help students in choosing a career and the ways in which the councelors help students use the choices. This study applied qualitative method. Data were collected by participatory observations and indepth interviews with students, their parents, and the councelors of Senior High Schools (SMU) in Malang, Sidoarjo, and Probolinggo. It was concluded taht the students successful in their career applied their personal, social, vacational, educational, leasure-time, religious, and democratic values in choosinga career. The approach applied by the councelors in helping their students was the Process Skill Approach, and the methods used were lecture, dialog or discussion, clarification, assignments, study tour, role playing, and career day